Correction: Functionalization of SiC/SiOx nanowires with a porphyrin derivative: a hybrid nanosystem for X-ray induced singlet oxygen generation. Issue 3 (12th May 2017) - Tatti, R.; Timpel, M.; Nardi, M. V.; Fabbri, F.; Rossi, F.; Pasquardini, L.; Chiasera, A.; Aversa, L.; Koshmak, K.; Giglia, A.; Pasquali, L.; Rimoldi, T.; et al.
Abstract : Correction for 'Functionalization of SiC/SiO x nanowires with a porphyrin derivative: a hybrid nanosystem for X-ray induced singlet oxygen generation' by R. Tatti et al., Mol. Syst. Des. Eng., 2017, DOI: ; Web:10.1039/c7me00005g .